2007
DOI: 10.4269/ajtmh.2007.77.929
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin/Chloroquine Combination Does Not Increase Cardiac Instability despite an Increase in Monophasic Action Potential Duration in the Anesthetized Guinea Pig

Abstract: Prolongation of the electrocardiogram QT interval by some, but not all drugs, has been associated with increased incidence of sudden cardiac death. Current preclinical regulatory assays cannot discriminate the arrhythmia liability of these drugs. Consequently, many new medications that prolong the QT interval are not developed despite their potential therapeutic benefit. Alternans (action potential duration alternations) is a measure of cardiac instability in humans and animals associated with the onset of ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 29 publications
(39 reference statements)
3
32
0
3
Order By: Relevance
“…15 Azithromycin itself does not usually cause clinically significant prolongation of the QTc interval, 16 but its use in combination with either chloroquine or hydroxychloroquine could theoretically increase the risk of TdP. Reassuringly, an animal model found no evidence of such an interaction, 17 and the combination has been used safely in patients with malaria. 18,19 Nevertheless, given limited experience in patients with COVID-19 and the potential for use of these drugs in patients with cardiac disease or those taking other drugs that delay repolarization, monitoring of the QTc interval at baseline and daily for the duration of treatment is advised, especially if azithromycin is coprescribed.…”
Section: Prolongation Of the Qtc Intervalmentioning
confidence: 99%
“…15 Azithromycin itself does not usually cause clinically significant prolongation of the QTc interval, 16 but its use in combination with either chloroquine or hydroxychloroquine could theoretically increase the risk of TdP. Reassuringly, an animal model found no evidence of such an interaction, 17 and the combination has been used safely in patients with malaria. 18,19 Nevertheless, given limited experience in patients with COVID-19 and the potential for use of these drugs in patients with cardiac disease or those taking other drugs that delay repolarization, monitoring of the QTc interval at baseline and daily for the duration of treatment is advised, especially if azithromycin is coprescribed.…”
Section: Prolongation Of the Qtc Intervalmentioning
confidence: 99%
“…Chloroquine is known to delay cardiac repolarization through inhibition of the potassium ion channel [116], increasing the chances of prolonging the electrocardiogram QT interval, while azithromycin does not [117]. The assessment of electrical alternans in an anesthetized guinea-pig showed that there is no additional risk of arrhythmia when azithromycin and chloroquine are used in combination; azithromycin may even be slightly protective of arrythmogenic risk when administered with chloroquine [118]. …”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…In 2007, Fossa and colleagues [Fossa et al 2007] pointed out that current preclinical regulatory assays may poorly determine the arrhythmia liability of drugs associated with QTc interval prolongation. This results in some drugs that link to QTc interval prolongation being dropped prematurely from further development.…”
Section: Introductionmentioning
confidence: 99%